Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12986-018-0274-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alpha-lipoic acid supplementation on inflammatory markers among patients with metabolic syndrome and related disorders: a systematic review and meta-analysis of randomized controlled trials

Abstract: ObjectiveThis systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted to determine the effect of alpha-lipoic acid (ALA) supplementation on the inflammatory markers among patients with metabolic syndrome (MetS) and related disorders.MethodsWe searched the following databases until November 2017: PubMed, MEDLINE, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials. Three reviewers independently assessed study eligibility, extracted data, and evaluated risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 48 publications
(58 reference statements)
5
31
0
2
Order By: Relevance
“…Due to its ability to reduce OS and serum uric acid level, to improve general antioxidant capacity by increasing GSH level and GPx activity or to down-regulate NF-kB [42,63] and upregulate heme-oxygenase-1 expressions [41], the AL discontinuous treatment ameliorates the elevation of serum CRP, thus preventing the systemic inflammatory process induced by chronic fructose consumption. Even if there are studies that support a decrease in inflammatory markers under a treatment with AL in humans, the available data in this context of inflammation are quite controversial, probably due to the different characteristics of population and the variety of studies design [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its ability to reduce OS and serum uric acid level, to improve general antioxidant capacity by increasing GSH level and GPx activity or to down-regulate NF-kB [42,63] and upregulate heme-oxygenase-1 expressions [41], the AL discontinuous treatment ameliorates the elevation of serum CRP, thus preventing the systemic inflammatory process induced by chronic fructose consumption. Even if there are studies that support a decrease in inflammatory markers under a treatment with AL in humans, the available data in this context of inflammation are quite controversial, probably due to the different characteristics of population and the variety of studies design [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review and meta-analysis of RCTs, findings showed that ALA supplementation decreased TNF-α, C-reactive protein (CRP), and interleukin-6 (IL-6) among patients with metabolic syndrome. 12 In a study on obese people, a significant reduction in CRP and TNF-α concentrations was observed following ALA supplementation. 18 In another study, ALA supplementation decreased TNF-α and IL-6 and increased adiponectin levels in obese subjects with impaired glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…11 Also, studies have shown that this antioxidant has beneficial effects in reducing serum lipids, inflammatory factors, oxidative stress, and CVD risk factors including HCY, OPG and Lp-PLA 2 . [12][13][14] We examined the effect of ALA supplementation on traditional CVD risk factors including cholesterol, HDL-C, LDL-C, triglyceride, etc. in another study that is currently under review.…”
Section: Introductionmentioning
confidence: 99%
“…Спектр клинического применения АЛК очень широк. Препараты АЛК приобрели большую популярность среди эндокринологов при лечении диабетической периферической вегетативной полинейропатии, а также проявлений метаболического синдрома [5]. В неврологии антиоксидантный эффект АЛК особенно важен для лечения ишемической патологии головного мозга (транзиторные ишемические атаки, ишемический инсульт), а также рассеянного склероза, для торможения прогрессирования болезни Альцгеймера [6,7].…”
Section: клиническое применениеunclassified